1994
DOI: 10.1152/ajpendo.1994.267.4.e591
|View full text |Cite
|
Sign up to set email alerts
|

Use of a leucine clamp to demonstrate that IGF-I actively stimulates protein synthesis in normal humans

Abstract: Insulin-like growth factor I (IGF-I) is thought to mediate the anabolic action of growth hormone. A glucose and amino acid clamp technique was used to investigate the effects of a 3-h intravenous infusion of either 43.7 pmol.kg-1.min-1 (20 micrograms.kg-1.h-1) IGF-I or 3.4 pmol.kg-1.min-1 (0.5 mU.kg-1.min-1) insulin on whole body leucine turnover in five normal human volunteers. During the IGF-I infusion, IGF-I levels increased (P < 0.01; 26.6 +/- 2.8 to 88.9 +/- 14.2 nmol/l) and insulin levels fell (P < 0.05;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 0 publications
4
25
0
Order By: Relevance
“…In general, administration in man or sheep of either rhIGF-1 (Clemmons et al 1992;Cottam et al 1992;Turkalj et al 1992;Elahi et al 1993;Russell-Jones et al 1994;Fryburg et al 1995;Oddy and Owens 1996) or LR 3 IGF-1 (Hocking Edwards et al 1994) provokes a rapid decline in plasma insulin, as was observed in the current study. Although the inter-animal variability was high, there was a trend for insulin concentrations to decline more following a 24-h infusion of LR 3 -IGF-1.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In general, administration in man or sheep of either rhIGF-1 (Clemmons et al 1992;Cottam et al 1992;Turkalj et al 1992;Elahi et al 1993;Russell-Jones et al 1994;Fryburg et al 1995;Oddy and Owens 1996) or LR 3 IGF-1 (Hocking Edwards et al 1994) provokes a rapid decline in plasma insulin, as was observed in the current study. Although the inter-animal variability was high, there was a trend for insulin concentrations to decline more following a 24-h infusion of LR 3 -IGF-1.…”
Section: Discussionsupporting
confidence: 70%
“…unbound to any of the IGFBPs. The LR 3 IGF-1 binds very poorly to IGFBP compared with endogenous or rhIGF-1; this results in greater potential biological activity and yields whole body responses Hocking Edwards et al 1994) at lower doses than used in trials using rhIGF-1 (Clemmons et al 1992;Turkalj et al 1992;Elahi et al 1993;Russell-Jones et al 1994). Despite this inherent difference in biological activity between rhIGF-1 and LR 3 IGF-1, it was decided to use similar doses of each, but at quantities known to yield responses with the native form (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is a lack of stimulation of wholebody protein synthesis with systemic infusion of IGF-I [271], which probably results from the fall in circulating insulin and/or amino acid concentrations that accompanies systemic IGF-I infusion in vivo. When amino acids [272] or insulin [273] is co-administered, IGF-I clearly stimulates whole-body protein synthesis.…”
Section: Igf-imentioning
confidence: 99%
“…rhIGF-I infusion has been shown to combine the insulin-like property of inhibiting proteolysis [13,14] with the GH-like property of stimulating protein synthesis [15]. The intracellular signalling mechanisms of IGF-I are not fully understood but it is likely that IGF-I acts, at least in part, by stimulating amino acid uptake into cells [16].…”
Section: Rhigf-i In Igf-i Deficiencymentioning
confidence: 99%